Evaluation of Financial Conflicts of Interest Among Physician‐Authors of American College of Rheumatology Clinical Practice Guidelines. Issue 9 (14th July 2020) - Wayant, Cole; Walters, Corbin; Zaaza, Zachary; Gilstrap, Carrie; Combs, Tyler; Crow, Hanna; Vassar, Matt
Abstract : Objective: Clinical practice guidelines (CPGs) underpin patient care, and ideally authors of these guidelines would be free from outside influence. However, it has been shown many times that authors of professional society CPGs receive large sums of money from industry drug companies, creating financial conflicts of interest. This study investigated industry payments catalogued in the Open Payments Database (OPD) that have been received by authors of the American College of Rheumatology (ACR) CPGs. Methods: Guidelines on the ACR web site that were published during or after August 2014 were used to retrieve the list of authors. All general, research, associated research, and ownership payments reported on the OPD between the date of publication of the CPG and 12 months prior were extracted in a parallel and blinded manner by 2 investigators. Results: Of the 89 US‐based physician‐authors from the 5 ACR CPGs identified within the study timeframe, 56 (62.9%) had received at least 1 payment according to OPD records. These 56 authors had received a median of 522 (interquartile range 119–2, 500), which, combined, was a total of 9, 728, 751. Nineteen authors had received at least 1 industry payment relevant to the CPG recommendations, for a median amount of 748 and a total of 1, 961, 362 in relevant payments. Of the total relevant payments received, a significant proportion was undisclosed (for ACR CPGs during or after August 2014, undisclosed payments were 699, 561, or 35.7% of the total). Conclusion: Fewer than one‐half of the US‐based physician‐authors of ACR CPGs during or after August 2014 had received guideline‐relevant industry payments. Nonetheless, a substantial proportion of the money received was not disclosed. Conflict of interest disclosure is a bare minimum requirement, and more permanent solutions may include divestiture or inclusion of more nonconflicted authors.